In the shadow of the constitution : the micro-politics of constitutional contestation in Cambodia / Ben Lawrence, University of Durham. - Lawrence, Ben (Writer on Cambodia's constitution) (Comparative constitutional law and policy ., 2025)
Across the world, the significance or role of Constitutions is too often understood in ways that ignore how they actually touch the lives or shape the political imaginations of ordinary people. Similarly, countries in the Global South, those that are not conventional liberal democracies, and those that have recently experienced conflict are generally underrepresented in the comparative constitutional law literature. Drawing on ethnographic insights and case-studies in Cambodia, this book provides a socio-legal account of constitutional practice under authoritarian rule and sheds light on how otherwise overlooked actors engage with constitutional language and assert constitutional agency. The Cambodian constitution is often dismissed as irrelevant, but its promises, principles and specific provisions actually matter deeply, both to the politically engaged and to ordinary people. This book highlights how many everyday contestations - over politics, religion and culture - take place In the Shadow of the Constitution.